2014
DOI: 10.1093/jxb/eru004
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced electrolyte leakage: the role of K+-permeable channels and involvement in programmed cell death and metabolic adjustment

Abstract: Electrolyte leakage accompanies plant response to stresses, such as salinity, pathogen attack, drought, heavy metals, hyperthermia, and hypothermia; however, the mechanism and physiological role of this phenomenon have only recently been clarified. Accumulating evidence shows that electrolyte leakage is mainly related to K(+) efflux from plant cells, which is mediated by plasma membrane cation conductances. Recent studies have demonstrated that these conductances include components with different kinetics of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
347
1
22

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 616 publications
(385 citation statements)
references
References 127 publications
15
347
1
22
Order By: Relevance
“…Consistent with previous observations, the OH $ -induced current was biphasic, composed of the instantaneous and the time-dependent depolarization-activated components (Fig. 6A), which could be tentatively assigned to ROS-activated NSCC and GORK, respectively (Demidchik et al, 2014;Shabala and Pottosin, 2014). Due to a strong outward rectification, a reversal potential of the time-dependent current could not be defined unequivocally; instantaneous currents reversed around 230 mV (i.e.…”
Section: Higher Sensitivity Of the Root Apex To Salinity May Be Relatsupporting
confidence: 86%
“…Consistent with previous observations, the OH $ -induced current was biphasic, composed of the instantaneous and the time-dependent depolarization-activated components (Fig. 6A), which could be tentatively assigned to ROS-activated NSCC and GORK, respectively (Demidchik et al, 2014;Shabala and Pottosin, 2014). Due to a strong outward rectification, a reversal potential of the time-dependent current could not be defined unequivocally; instantaneous currents reversed around 230 mV (i.e.…”
Section: Higher Sensitivity Of the Root Apex To Salinity May Be Relatsupporting
confidence: 86%
“…It is also possible that ROS-induced cytosol Ca 2+ elevations (reviewed in Mori and Schroeder 2004), in turn, can inhibit PM H + -ATPase activity (Brault et al 2004;Kinoshita et al 1995;Polevoi et al 1996), and depolarise plasma membrane potential (Trouverie et al 2008). It can be also speculated that the inhibition of IAA-induced growth may also be caused by an ROS-induced K + efflux, which results in a dramatic K + loss from plant cells (reviewed in Demidchik et al 2014). Here, the suggestion that NQ and NQ-2-OH inhibit PM H + -ATPase is supported by four pieces of evidence: (1) the inhibition of IAA-induced proton extrusion by both naphthoquinones (excluding NQ at 1 µM, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This occurred due to an increase in H2O2, resulting in membrane disturbs and release of electrolytes, with consequent reduction in permeability of the cell membrane (GonzalezMendoza et al, 2009;Demidchik et al, 2014;Langaro et al, 2014). Masoumi et al (2010) observed an increase in EL in Kochia scoparia leaves, corroborating with the data of this study.…”
Section: Discussionmentioning
confidence: 99%